A Proposal for a Scientifically-Informed and Instrumentalist Account of Free Will and Voluntary Action - Racine, Eric (Frontiers in Psychology, 2017)
The ability to choose freely is captured under the umbrella concept of “free will”, which designates an ability that plays a crucial role in most understandings of autonomy and responsibility and, thus, bears significance for moral practice and moral theory. Some claim that neuroscience research challenges the existence of free will/voluntary action while some who adopt stronger eliminativist stances have gone as far as describing free will as an illusion. Contrary to that, those relying on realist stances have restated the foundational value and role of folk psychological concepts of voluntary action and free will in, for example, the domains of ethics and law. An emerging body of research in cognitive science and social psychology has generated results suggesting that the phenomena captured by the concepts describing free will and voluntary action are dynamic and responsive to priming and framing effects. We propose that this body of research suggests the existence of dynamic and consequential properties of free will better captured following pragmatist theory and instrumentalist epistemology. This contrasts the simpler static concept of free will and the related metaphysics that was at the basis of earlier debates and structured around the poles of realism and eliminativism. This paper contextualizes ontological and epistemological debates about free will, describes a scientifically-informed and instrumentalist account of the concept of free will and voluntary action consistent with recent research in cognitive science, and discusses its implications for research (e.g., theoretical assumptions of research paradigms, interdisciplinary research) and practice (e.g., impact on self-image and social behavior).